Pertanggungjawaban Pemidanaan terhadap Kreator Konten Bermuatan Pornografi di Platform Media Sosial X (Pusat Riset dan Inovasi Nasional, 2026)
The development of technology in the era of globalization has brought significant changes in society, particularly through the emergence of the internet and social media such as WhatsApp, X (Twitter), Facebook, Instagram, Telegram, and TikTok, which facilitate rapid information dissemination. This development has also given rise to a new profession, namely content creators, who produce and share content in the form of images, videos, or text for branding, professional purposes, or self-expression, often resorting to sensationalism to attract audience attention. On the other hand, the ease of access to social media has also triggered the spread of negative content, including pornography, as evidenced by Komdigi/Kominfo data showing millions of blocked negative content, with X being one of the dominant platforms. In Islamic perspective, anything that leads to adultery is prohibited as stated in QS. Al-Isra verse 32. A prominent case is Dea OnlyFans (Gusti Ayu Dewanti) who was arrested for distributing pornographic content through OnlyFans and Google Drive, charged under the Pornography Law and ITE Law, and found guilty in the Supreme Court Decision Number 2086 K/Pid.Sus/2023. This study discusses 1) How are the differences in judges' considerations at the District Court, High Court, and Cassation? 2) Can the Supreme Court judges' considerations provide a deterrent effect? This research uses a descriptive method with normative legal research based on literature study, using primary, secondary, and tertiary legal materials.